2023
DOI: 10.3390/jpm13091364
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profile of Variants in CDH1, TP53, PSCA, PRKAA1, and TTN Genes Related to Gastric Cancer Susceptibility in Amazonian Indigenous Populations

Kaio Evandro Cardoso Aguiar,
Izabela De Sousa Oliveira,
Amanda De Nazaré Cohen-Paes
et al.

Abstract: Gastric Cancer is a disease associated with environmental and genetic changes, becoming one of the most prevalent cancers around the world and with a high incidence in Brazil. However, despite being a highly studied neoplastic type, few efforts are aimed at populations with a unique background and genetic profile, such as the indigenous peoples of the Brazilian Amazon. Our study characterized the molecular profile of five genes associated with the risk of developing gastric cancer by sequencing the complete ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Previous research also found mitigating differences between the genetic profile of indigenous peoples and those of the other five world populations examined here [60][61][62]. However, the physical and geographic isolation of these peoples contributes to a gap in epidemiologic and genetic information.…”
Section: Discussionmentioning
confidence: 47%
“…Previous research also found mitigating differences between the genetic profile of indigenous peoples and those of the other five world populations examined here [60][61][62]. However, the physical and geographic isolation of these peoples contributes to a gap in epidemiologic and genetic information.…”
Section: Discussionmentioning
confidence: 47%